UPAYA PENGUATAN NILAI RELIGIUS PESERTA DIDIK MELALUI PROGRAM TAHSIN AL-QUR'AN DI SMP ISLAM KARAWANG - Anastasya, Arum; Hinggil Permana; Agus Susilo Saefullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the effect of the Qur’an Tahsin Program on strengthening students’ religious values at an Islamic junior high school in Karawang. The study employed a quantitative approach using a survey method and a descriptive correlational design. The sample consisted of 81 students selected through saturated sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed through normality and linearity tests, simple linear regression, the coefficient of determination, and hypothesis testing using SPSS. The findings indicate that the Qur’an Tahsin Program had a positive and significant effect on students’ religious values, with a significance value of 0.004. The program contributed 9.8% to the development of religious values, while the remaining 90.2% was influenced by factors outside the model. Regular Qur’an reading, teacher guidance and correction, motivation, and reinforcement supported the development of discipline, responsibility, Qur’an-reading habits, and awareness of practicing Islamic values. The novelty of this study lies in providing quantitative evidence of the contribution of the Tahsin Program to the religious character of junior high school students based on B. F. Skinner’s behaviorist theory.